Development of early detection of low-birth-weight instrument based on maternal risk factors: A mixed-methods study - Sri Utami; Rekawati Susilaningrum; Nursalam Nursalam; Erna Siti Zulaecha; Sri Rahayu (JKP (Jurnal Keperawatan Padjajaran), 2023)
Background: Babies born with low birth weight (LBW) are at a higher risk of experiencing health problems. The absence of quick and reliable instruments to detect LBW conditions can significantly impact the growth and development of newborns.